Correlational study on self-compassion and college adjustment among university freshmen during distance learning - Aini, Indani Durrotul; Widyasari, Pratiwi (International Journal of Research in Counseling and Education, 2021)
When entering college, first-year students faced new challenges. College adjustment is necessary in the early period of college because it can predict college success. Covid-19 pandemic hinders college adjustment due to distance learning. Meanwhile, a previous study conceptually mentioned that self-compassion supported college adjustment. This study examined the correlation between self-compassion and college adjustment among first-year college students in distance learning during Covid-19 pandemic. Undergraduate students batch 2020 (N = 381) were surveyed using Self-Compassion Scale and Student Adaptation to College Questionnaire. Pearson’s correlation test showed a positive significant correlation between self-compassion and college adjustment. The strongest correlation was found between isolation and personal-emotional adjustment. These findings indicated that self-compassion tends to help a better college adjustment in a distance learning context.